Application of IPv6 for State Grid Corporation Company Smart Grid - Biyao Huang; Jinghong Guo; Nan Quan; Yang Wang; Huixia Ding; Guojun Liu; Jie Tong; Geng Zhang; Nan Wang (Dianxin kexue)
Smart grid must be open, distributed architecture, there are multiple internet, addressable, independently managed entity. Smart grid need to build a data communication network to support the exchange data freely and safely among all the components. The state grid corporation smart grid status and data communication network were described. IPv6 application is internal demand for smart grid construction, and the IPv6 technology applications in the smart grid is important, after that the standard development planning and existing international standards development status were analyzed, and finally the data communication network transition to IPv6 practical work was described. This analysis work for the next generation of internet technology in the smart grid application can be a reference for the smart grid development.